2014
DOI: 10.1074/jbc.m113.527754
|View full text |Cite
|
Sign up to set email alerts
|

Down-modulation of SEL1L, an Unfolded Protein Response and Endoplasmic Reticulum-associated Degradation Protein, Sensitizes Glioma Stem Cells to the Cytotoxic Effect of Valproic Acid

Abstract: Background: Valproic acid is considered as a promising anti-cancer therapeutic agent acting on unfolded protein response. SEL1L is an UPR-responsive gene. Results: SEL1L interference synergy enhances VPA cytotoxic effects on glioma stem cells. Conclusion: VPA treatment combined with SEL1L depletion may influence GSC pharmacological response. Significance: Targeting SEL1L in association with valproic acid treatment may improve glioma treatment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
16
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 25 publications
(19 citation statements)
references
References 45 publications
1
16
0
Order By: Relevance
“…Within GBM cell lines, the SNP rs12435998 down-regulates SEL1L expression only in NS and, at the same time, it increases the sensitivity to VPA, confirming a previous observation [ 21 ]. In fact, compared to wild type NS, the cell viability after VPA was significantly lower in NS with the TC/CC variant genotype.…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…Within GBM cell lines, the SNP rs12435998 down-regulates SEL1L expression only in NS and, at the same time, it increases the sensitivity to VPA, confirming a previous observation [ 21 ]. In fact, compared to wild type NS, the cell viability after VPA was significantly lower in NS with the TC/CC variant genotype.…”
Section: Discussionsupporting
confidence: 86%
“…SEL1L is involved in several other neoplasia [ 16 20 ]. Its reduced protein expression by RNA interference increases GBM stem cell sensitivity to valproic acid (VPA) treatments [ 21 ]. SEL1L also plays a role in the neural stem cell self-renewal [ 22 ].…”
Section: Introductionmentioning
confidence: 99%
“…mSEL‐1L was well expressed during CNS development (Donoviel, Donoviel, Fan, Hadjantonakis, & Bernstein, ) and its deficiency led to severe defects in brain, in addition to general organogenesis and maintenance (Francisco et al, ). Previously was shown the essential function of mSEL‐1L in guaranteeing the balance between self‐renewal and differentiation in neural progenitors (Cardano et al, ), possibly by controlling the fine tuning levels of self‐renewal and fate determinant regulators (Cardano et al, ; Cattaneo et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…Mellai et al [2020] reported that overexpression of SEL1L in malignant gliomas is associated significantly with TERT promoter mutation, EGFR gene amplification, and other well-known negative prognostic markers for gliomas, leading the authors to suggest a role for SEL1L in glioma progression. Furthermore, downregulation of SEL1L conferred positive sensitivity to valproic acid treatment [Cattaneo et al, 2014] which may suggest a role of SEL1L in gene-target therapy.…”
Section: Discussionmentioning
confidence: 93%